Pemberdayaan Pengusaha Orang Asli Papua (OAP) dalam Kebijakan Pemerintah Kota Jayapura - Itaar, Alberto Freed; Silo, Akbar; Tebay, Vince; Kaiwai, Hans Z (JURNAL EKOLOGI BIROKRASI, 2025)
This study aims to analyze the dynamics of empowering Indigenous Papuan Entrepreneurs (OAP) within the Jayapura City Government’s policy framework during Papua’s Special Autonomy (Otsus) Phase II, focusing on barriers, opportunities, and strategies to strengthen business independence. A qualitative descriptive method with a case study approach was applied, using in-depth interviews, observations, and policy document analysis. The findings reveal that affirmative policy implementation is hindered by weak managerial capacity, low digital literacy, traditional business institutions, and identity manipulation practices by non-OAP entrepreneurs, which distort empowerment goals and perpetuate dependency. Nevertheless, strategic opportunities remain through special regulatory support, the SIKaP OAP digital application, and a collaborative penta-helix model involving government, private sector, academia, and local communities. The study concludes that affirmative policy reform is needed to be more contextual, participatory, and capacity-based, with recommendations to strengthen digital literacy, ensure fair access to capital, reinforce OAP institutions, and implement transparent monitoring and evaluation, thereby enabling OAP’s economic independence and positioning them as key actors in Jayapura’s economic development.